2007
DOI: 10.1088/0022-3727/40/16/010
|View full text |Cite
|
Sign up to set email alerts
|

Two-temperature chemically non-equilibrium modelling of anairsupersonic ICP

Abstract: In this work, a non-equilibrium mathematical model for an air inductively coupled plasma torch with a supersonic nozzle is developed without making thermal and chemical equilibrium assumptions. Reaction rate equations are written, and two coupled energy equations are used, one for the calculation of the translational–rotational temperature Thr and one for the calculation of the electro-vibrational temperature Tev. The viscous dissipation is taken into account in the translational–rotational energy equation.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…At the beginning of the 1980s, Chen et al [38] introduced a two-temperature model of dc arcs. Non-LTE also occurs when injecting a cold gas into a plasma jet [39], when quenching the plasma to promote the formation of chemical species that are produced by recombining radicals in a given temperature range [40], near electrodes and walls [41][42][43][44][45][46][47][48], in expanding plasma jets under soft vacuum [49][50][51][52][53] and in arc jets [54]. A further example is the new spray device of Sulzer-Metco, devoted to the deposition of columnar structures from the vapour phase in a chamber at a few tens of pascals [55].…”
Section: Non-lte and Chemical Equilibriummentioning
confidence: 99%
“…At the beginning of the 1980s, Chen et al [38] introduced a two-temperature model of dc arcs. Non-LTE also occurs when injecting a cold gas into a plasma jet [39], when quenching the plasma to promote the formation of chemical species that are produced by recombining radicals in a given temperature range [40], near electrodes and walls [41][42][43][44][45][46][47][48], in expanding plasma jets under soft vacuum [49][50][51][52][53] and in arc jets [54]. A further example is the new spray device of Sulzer-Metco, devoted to the deposition of columnar structures from the vapour phase in a chamber at a few tens of pascals [55].…”
Section: Non-lte and Chemical Equilibriummentioning
confidence: 99%
“…This Re result suggests that the flow is in transition state with both turbulent and laminar transports [22]. On the other hand, Morsli [23] reported that the turbulence is present in the cooler regions (below 5000 K) of ICP torch jets. Also it is detailed that the laminar flow is promoted due to the lower densities and higher viscosities at the centre of the plasma stream (above 5000 K).…”
Section: Turbulence Characteristicsmentioning
confidence: 90%
“…To study theoretically this kind of discharge, taking into account the possible occurrence of departures from thermal equilibrium, it is necessary to develop multi temperature MHD models. There are more and more publications in the literature dealing with multi-T fluid models such as the works of Mostaghimi et al [2], El Morsli and Proulx [3], Tanaka [4], Ye et al [5] and Al-Mamun et al [6] concerning respectively argon, air, Ar-N 2 , Ar-H 2 and Ar-CO 2 -H 2 radio-frequency inductively coupled plasma (ICP) torches, Ghorui et al [7] for the study of the oxygen flow inside the nozzle of a metal cutting device, Boselli et al [8] concerning a direct current (DC) welding arc in argon, Trelles et al [9], Bartosiewicz at al. [10] and Kaminska et al [11] for the study of a DC plasma torch in argon, Baeva and Uhrlandt [12] and Freton et al [13] concerning free-burning arcs in argon, Colombo et al [14] for a 3D transient model of a twin torch system, Park et al [15] for a DC transferred arc in argon and Benilov and Naidis [16] for the study of a wall-stabilized DC arc discharge.…”
Section: Introductionmentioning
confidence: 99%